Utilisation of Mussel Shell Ash and Palm Oil Leaves Ash as Admixture in Concrete - Bakar, Muhammad Khairus Sholihin; Othman, Nor Hazurina; Sainudin, Muhammad Shabery; Khalid, Faisal Sheikh; Muthusamy, Khairunisa (International Journal of Integrated Engineering, 2020)
Mussel shell and palm oil leaves is a type of waste that generally undergo disposal process due to less-valuable materials. However, this waste are potentially to be used in concrete designing due to its cementing properties. Thus, this paper presenting the incorporation of mussel shell ash (MSA) and palm oil leaves ash (POLA) as an admixture in concrete.  MSA and POLA were obtained through grounding, burning and sieving process. As total, 84 concrete samples were mixed with different proportions of POLA (0.5%, 1% and 1.5%), MSA (1% and 2%) and K for control samples. All the samples were cured for 7 days and 28 days. The study was carried out to measure its physical and mechanical properties such as compressive, split tensile and capillary absorption analysis. While, its materials properties (MSA and POLA) were identified through its specific gravity test. The results demonstrated that B5 (1.5% POLA + 1% MSA) gave a good performance in concrete compressive strength on 7 and 28 days. Besides that, B5 also indicates a lower capillary water absorption compared to other specimens. Whereas B6 indicates a higher value for density analysis. Overall, the experimental result indicates that B5 does not giving any adverse effect on the concrete performance. Thus, it is prove that the utilisation of MSA and POLA as cementing materials are applicable in improving concrete strength and its durability accordingly to the selected percentages.